A first approach to the use of upconversion nanoparticles to measure fluorescent tracers in water: a proof of concept. (20th October 2021) - Bujjamer, Juan M; Illescas, Marcos; Marchi, M Claudia; Grecco, Hernán E; Barja, Beatriz C
Abstract: In this work we use lanthanide based NaYF4 :Er 3+, Yb 3+ upconversion nanoparticles (UCNP) to detect ppb-level sensitibity of a xanthene dye, Rhodamine B (RB) dye, under NIR excitation. A static energy transfer was observed between the luminescent UCNP energy donors and RB acceptor in aqueous solution for three different sizes of UCNP. No specific covalent functionalization of the UCNPs was performed providing a direct method of detection, particularly promising in natural systems where the interfering fluorescence background is a detrimental limitation to the performance of the detection method. This procedure is a first approach to be applied in estuarine and coastal zone where the high content of suspended particulate matter prevents the detection of tracers.